2018
DOI: 10.1186/s13020-018-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood and urinary metabolomic evidence validating traditional Chinese medicine diagnostic classification of major depressive disorder

Abstract: BackgroundMajor depressive disorder (MDD) is a highly heterogeneous disease. Further classification may characterize its heterogeneity. The purpose of this study was to examine whether metabolomic variables could differentiate traditional Chinese medicine (TCM) diagnostic subtypes of MDD.MethodsFifty medication-free patients who were experiencing a recurrent depressive episode were classified into Liver Qi Stagnation (LQS, n = 30) and Heart and Spleen Deficiency (HSD, n = 20) subtypes according to TCM diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Thus, perturbations in SCFA and AA in the central, as well as peripheral system, seem to be involved in the pathogenesis of depression. Studies conducted on human cerebral fluid or plasma samples, also observed pronounced differences in AA concentrations between healthy and depressed individuals [22,29]. Moreover, alterations of five metabolites involved in the ABC transport system were observed in depressed monkeys compared to their healthy counterparts.…”
Section: Metabolomics In Depression Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, perturbations in SCFA and AA in the central, as well as peripheral system, seem to be involved in the pathogenesis of depression. Studies conducted on human cerebral fluid or plasma samples, also observed pronounced differences in AA concentrations between healthy and depressed individuals [22,29]. Moreover, alterations of five metabolites involved in the ABC transport system were observed in depressed monkeys compared to their healthy counterparts.…”
Section: Metabolomics In Depression Modelsmentioning
confidence: 92%
“…More specifically, animal depression studies revealed that amino acid (AA) metabolism is disturbed in various brain regions, but also in the plasma of depressed individuals. Especially the glutamate-γ-aminobutyric acid (GABA)-glutamine cycle, which has been implicated to be related to the pathogenesis of MDD, due to its key role in maintaining the supply of neurotransmitters [22]. Overall, the glutamatergic system plays an important role in the pathophysiology of mood disorders, such as depression, where glutamate disturbances in the brain have been linked to the neuroplasticity hypothesis of MDD [23].…”
Section: Metabolomics In Depression Modelsmentioning
confidence: 99%
“…Tai Chi Chuan is often viewed by Chinese people as physical exercise to improve mind–body health, therefore, making it an interesting research target in the field of cardiovascular health and anxiety symptoms. Thus, a randomized-controlled trial was conducted to evaluate the effect of a Tai Chi Chuan exercise program on anxiety status and blood lipid profile in individuals with hypertension as compared to healthy subjects [ 132 ]. As an increase in HDL and a decrease in total cholesterol, LDL, and triglycerides went along with decreases in trait and state anxiety, it was suggested that Tai Chi might be used as an alternative treatment in patients with anxiety disorders.…”
Section: Metabolomics In the Study Of Anxiolytic Effectsmentioning
confidence: 99%
“…TCM is an ancient medical practice with a unique diagnostic system. A key method of diagnosis is to differentiate the etiology and pathogenesis, which are usually determined by the comprehensive analysis of clinical symptoms and signs collected through inspection, auscultation, olfaction, interrogation and pulse palpation (13). These are also known as TCM Syndromes according to which clinicians choose suitable treatments.…”
Section: Introductionmentioning
confidence: 99%